Risk factors of vitamin D deficiency in children with epilepsy taking anticonvulsants at initial and during follow-up - Seung Ho Lee; Jeesuk Yu (Korean Society of Pediatric Endocrinology, 2015)
PurposeVitamin D status was evaluated in children with epilepsy taking anticonvulsants to determine the prevalence and risk factors of vitamin D deficiency.MethodsThis study was designed as both a cross-sectional and a retrospective cohort study. A sum of 198 children who were diagnosed with epilepsy at the Department of Pediatrics in Dankook University Hospital was included. Their serum vitamin D levels were reviewed based on clinical information, and analyzed using IBM SPSS ver. 20.0.ResultsOne hundred twenty-four children (62.6%) had vitamin D deficiency. Two risk factors were associated: winter to spring season (odds ratio [OR], 3.71; 95% confidence interval [CI], 1.835-7.492) and age more than 12 years (OR, 3.22; 95% CI, 1.377-7.542). Out of the 57 patients who were not vitamin D deficient at the time of initial assay, 47 patients (82.5%) became vitamin D deficient during followup. The change of serum 25-hydroxy vitamin D3 (25(OH)D) levels during follow up showed a weak negative correlation with the duration of medication (r=-0.283, P=0.033). Medication duration was longer and brain magnetic resonance imaging (MRI) abnormality, abnormal underlying conditions, and nonambulatory status were more frequently present in twenty-five patients (44%) who showed a decline of more than 15 ng/mL during follow-up (P<0.05).ConclusionVitamin D deficiency is common in children with epilepsy taking anticonvulsants, especially in adolescents more than 12 years of age. This study emphasizes the regular monitoring of vitamin D level, especially in the presence of longer duration of medication, brain MRI abnormality, abnormal underlying conditions, and nonambulatory status.